Avoidable losses: High-stakes accountability and the dropout crisis. - McNeil, Linda McSpadden; Coppola, Eileen; Radigan, Judy; Vasquez Heilig, Julian (Education Policy Analysis Archives, 2008)
In the state of Texas, whose standardized, high-stakes test-based accountability system became the model for the nation's most comprehensive federal education policy, more than 135,000 youth are lost from the state's high schools every year. Dropout rates are highest for African American and Latino youth, more than 60% for the students we followed. Findings from this study, which included analysis of the accountability policy in operation in high-poverty high schools in a major urban district, analysis of student-level data for more than 271,000 students in that district over a seven-year period under this policy, and extensive ethnographic analysis of life in schools under the policy, show that the state's high-stakes accountability system has a direct impact on the severity of the dropout problem. The study carries great significance for national education policy because its findings show that disaggregation of student scores by race does not lead to greater equity, but in fact puts our most vulnerable youth, the poor, the English language learners, and African American and Latino children, at risk of being pushed out of their schools so the school ratings can show "measurable improvement." High-stakes, test-based accountability leads not to equitable educational possibilities for youth, but to avoidable losses of these students from our schools.